O uso do princípio de indução matemática no ensino básico - Goiaz Junior, Gethsemani Saraiva de (2023)
The principle of finite induction is a useful and rigorous tool for mathematical proofs whose conjectures are related to the set of natural numbers. However, the use of this principle for verifications in basic education is still greatly underutilized. In this work, we intend not only to demonstrate the importance of using this strong principle but also to provide study material and support for students and teachers, based on the National Common Curricular Base (BNCC). We present various demonstrations for elementary and secondary education, covering several proposed content in these stages of education. We suggest propositions for further exploration, which can be used as pathways for high school education. We also believe that this work can spark interest and expand the use of the principle of finite induction in the teaching of mathematics and other curriculum components.